Penyuluhan Implementasi Kebijakan Layanan di Masa Covid-19 dan Kaitannya Dengan Kinerja Perawat di Rumah Sakit Umum Sembiring - Yunita Syahputri Damanik; Viktor Edward Marbun; Rian Fedriko Ginting (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
The purpose of health development is health is to create people who have healthy behavior which includes awareness, willingness and ability to live healthy, able to reach quality health, live in a healthy environment and have optimal health degrees. The creation of an Indonesian society like this is marked by the population living with a healthy behavior and environment, and having the ability to access health services. Health services are every effort that is carried out alone or jointly in an organization to maintain and improve health, prevent and cure disease and restore the health of individuals, families, groups and or communities. The use of health services is most closely related to when a person needs health services and how far a person takes health services. In supporting development in the health sector, hospitals have a role in implementing policies in the health sector. It is mandated that to carry out its duties in health development, hospitals have the role of carrying out individual health service efforts in a plenary manner. The policy that regulates the Hospital is PERMENKES No. 3 of 2020 concerning Hospital Classification and Licensing states that a hospital is a health service institution that provides complete individual health services that provide inpatient, outpatient, and emergency services. This counseling activity aims to explain the implementation of service policies in hospitals during the Covid 19 pandemic. From the findings it is known that the Sembiring Deli Tua General Hospital has carried out its functions as mandated by PERMENKES No. 3 of 2020, namely the function as a complete individual health service that provides inpatient, outpatient, and emergency services. However, a special strategy is needed to maintain the quality of service in the hospital to obtain achievements in accordance with the minimum service standards contained in the performance assessment.